(untitled) (IUPHAR/BPS Guide to Pharmacology CITE, 2019)
Thyrotropin-releasing hormone (TRH) receptors (provisional nomenclature as recommended by NC-IUPHAR [13]) are activated by the endogenous tripeptide TRH (pGlu-His-ProNH2). TRH and TRH analogues fail to distinguish TRH1 and TRH2 receptors [28]. [3H]TRH (human, mouse, rat) is able to label both TRH1 and TRH2 receptors with Kd values of 13 and 9 nM respectively. Synthesis and biology of ring-modified L-Histidine containing TRH analogues has been reported [22].